Continuous facile synthesis of nano-sized zinc oxide and its optical properties. (11th July 2018) - Akram, Muhammad; Razali, Ili Rabihah; Ghafoor, Faisal; Ur-Rahman, Shams; Butt, Faheem K; Hussain, Rafaqat
Abstract: Zinc oxide (ZnO) was synthesized by using continuous microwave (Mw) flow synthesis. The synthesized nanoparticles were characterized by x-ray diffraction and transmission electron microscopy techniques to study the phase composition, particle size and morphology. Transmission electron microscopy studies revealed an increase in the particle size from 6–12 nm upon increasing the reaction time. Photoluminescence (PL) studies were utilized to explore the surface defects and oxygen vacancies present in the ZnO. PL results confirmed a gradual decrease in the intensity of surface oxygen vacancies and defects of ZnO nanoparticles on increasing the dwell time inside the Mw. Similarly, energy bandgap studies showed a red shift in the energy bandgap from 3.19 eV to 2.91 eV with change in the reaction time. A red shift in energy bandgap is a good sign as it can enhance the utilization of ZnO nanoparticles in many of visible range applications such as optoelectronics and solar cells industry.